Current treatment approaches for breast cancer patients with HER2-positive disease in the adjuvant, and neo-adjuvant setting - Surti, Rashmi Purushottam (International Journal of Basic & Clinical Pharmacology, 2021)
Breast cancer (BC) is the second most common cancer and the leading cause of mortality among women globally. Approximately 20% to 25% of BC patients have amplification of the human epidermal growth factor receptor 2 (HER2) genes, a marker of poor prognosis. However, the introduction of anti-HER2- therapies (trastuzumab, followed closely by lapatinib, pertuzumab, and T-DM 1) has changed the natural history of HER2-positive BC and improved the prognosis and survival in HER2-positive BC patients. The approval of trastuzumab and pertuzumab linked with a taxane as a first-line treatment and follow-up treatment with the antibody-drug conjugate T-DM1 has undeniably contributed to attaining these outcomes. The Tyrosine Kinase Inhibitor lapatinib is another commonly used treatment in combination with capecitabine, approved on the basis of an improvement in progression-free survival. The superiority of combination anti-HER2 therapy to achieve more complete inhibition of the various HER receptor dimers has been demonstrated in clinical studies. Nonetheless, studies have also suggested that some HER2-amplified tumors may benefit from anti-HER2 therapy combined with only a single chemotherapy agent or in the absence of any chemotherapy. However, despite therapeutic advances, tumors expressing estrogen receptor (ER) have poorer responses to targeted therapy and are more likely to relapse. A better understanding of resistance to existing anti-HER2 agents, along with the role played by the microenvironment and of interconnected signaling pathways, can permit tailor-made therapeutic options for each patient. The aim of this review is to evaluate treatment approaches for BC patients with HER2-positive disease in the adjuvant, and neoadjuvant setting.